Zu eigen + Ing + Adolf + Hermann + Fischer + / [O. Feil]. - Feil, Otto (1894-1985) (1929)
W kwadracie utworzonym z napisu: Zu eigen + Ing + Adolf + Hermann + Fischer +, wpisane koło zębate z literami A. H. F. Sygn. aut. pod kompoz.